Vaccination with synthetic long peptide and CpG 2395 in AddaVax induces potent anti-tumor effects - Shanshan Jiang; Shuqi Zhao; Qiaojiajie Zhao; Yinfang Wang; Weihua Zhang; Yangmeng Feng; Lijie Zhang (Experimental Biology and Medicine)
Cancer/testis antigen HCA587, also known as MAGE-C2, highly expressed in a wide range of malignant tumors with unique immunological characteristics, serves as a potential target for tumor immunotherapy. Synthetic long peptides from HCA587 (HCA587 SLP) were proved to be highly immunogenic and promising in the application of cancer vaccine composed of Freud’s adjuvant (FA) and CpG 1826, whereas, scarce CD8+ T cell response may limit their anti-tumor effects during previous research. In this study, notwithstanding the multiple potential of IFN-α in immune modulation, there was no evidence of IFN-α in enhancing the immune response elicited by HCA587 SLP vaccine (HCA587 SLP + FA + CpG 1826). Given the unpleasant side-effects of Freud’s adjuvant, then we applied AddaVax as a substitute for Freud’s adjuvant, and we demonstrated that HCA587 SLP, formulated with AddaVax and CpG 2395, could induce more robust immune response in comparison with combined use of AddaVax and CpG 1826 through ELISpot assay. Furthermore, both IFN-γ-secreting CD4+ T cell and CD8+ T cell responses could be elicited by HCA587 SLP in combination with AddaVax and CpG 2395, and CD8+ T cell response was most obviously observed under the condition of 10-h inhibition of cytokine secretion by brefeldin A post 10-h stimulation with HCA587 SLP, suggesting that cross presentation of exogenous long peptides to CD8+ T cells may require more time than direct presentation to CD4+ T cells. This vaccine formulation also conferred protection against challenge with HCA587-expressing B16 melanoma presented by delayed tumor growth and prolonged survival compared. This formulation of HCA587 SLP vaccine holds promise for the treatment of patients with cancer in future clinical trials.